Rising out of hatred [compact disc, unabridged] : the awakening of a former white nationalist - Saslow, Eli (Random House Audio, 2018)
Derek Black grew up at the epicenter of white nationalism, then he went to college. When his supremacist views were confronted, Derek first opened his eyes, then his heart and mind, to reality.